Sustainable synthesis and advanced optimization of Prosopis juliflora biomass catalyst for efficient biodiesel production and environmental impact assessment - Thota S S Bhaskara Rao; Manikandaraja Gnanaprakasam; Rajayokkiam Manimaran; Dhinesh Balasubramanian; Utku Kale; Artūras Kilikevičius (Scientific Reports)
Abstract The present research focuses on developing an innovative biochar-based heterogeneous catalyst from Prosopis Juliflora biomass waste using response surface methodology and genetic algorithm (GA) to optimize pyrolysis parameters, achieving a 46.31% PJBC yield from 60 mg of biomass at 790 °C for 60 min. The pyrolyzed PJBC is characterized using SEM, FTIR, XRD, EDX, BET, XPS analyses, and physico-chemical measurements to confirm its catalytic activity. Now, the newly synthesized PJBC serves as an efficient catalyst for waste Trichosanthes cucumerina seed biodiesel (WTSB) production from waste Trichosanthes cucumerina seed bio-oil through trans-esterification, achieving a maximum yield of 97.42%. Also, the WTSB exhibits excellent physico-chemical properties that meet most of the ASTM D6751 standards for biodiesel and closely align with the characteristics of conventional diesel fuel. Therefore, this research utilized neat WTSB and WTSB/diesel blends (WTSB25, WTSB50, and WTSB75) in a direct injection (DI) diesel engine at variable load settings. Among all WTSB blends, the WTSB25 blend showed closer variations of 1.65% lower BTE and 9.29% higher BSEC when compared to conventional diesel fuel readings. Its peak in-cylinder pressure and heat release rate were similar to those of diesel fuel at 100% engine load. Emission analysis indicated that the WTSB25 reduced specific HC, CO, and smoke opacity emissions by 8.39%, 13.97%, and 4.18%, respectively. However, specific NO emissions increased slightly by 3.05% compared to diesel fuel. Thus, WTSB25 is validated as a viable diesel alternative requiring no significant engine modifications. The environmental impact, lifecycle and economic feasibility are also discussed.